Who Did What: An Illustrated Biographical Dictionary - Mitchell Beazley Publishers (Peerage Books, 1990)
Brief alphabetically arranged biographical sketches of 5000 men and women representing a variety of professions and nationalities.
Keywords: Biographies-Dictionaries-Reference